Fostering Healthy Minds: The Role of Inclusivity in Empowering Youth in Karang Taruna - Wartini, Sri; Prananta, Widya; Febriatmoko, Bogy; Hendriyani, Rulita; Hendrajaya (Indonesian Journal of Devotion and Empowerment, 2025)
Inclusivity emphasizing the acceptance and appreciation of diversity without discrimination is crucial in youth organizations such as Karang Taruna, a village-level platform for adolescent development in Indonesia. This community service paper examines the role of inclusivity in strengthening adolescent mental health within Karang Taruna Kalisegoro, Gunungpati, Semarang. The initiative was carried out by a multidisciplinary team from Universitas Negeri Semarang (Unnes) through a one-day workshop on mental health literacy and inclusive leadership for 20 administrators and members of Karang Taruna. The methods included interactive lectures, case analysis using documentary films on adolescent mental health disorders, peer tutorials, and facilitated group discussions, grounded in Ryff’s Psychological Well-Being Model. Results revealed a significant increase in participants’ understanding of mental health issues, early recognition of mental disorder symptoms, reduced stigma, and commitment to establishing a mental health-aware community integrated with Karang Taruna and the village government. Participants also reported enhanced confidence in inclusive leadership and the ability to foster mutually supportive environments, supporting all six dimensions of Ryff’s psychological well-being. Recommendations include sustained cross-sector collaboration, expansion of literacy programs, and further empirical research to measure the long-term impact of inclusivity on adolescent mental health indicators.